Policing and mental health: a rapid evidence assessment of the effect of police activity on people's mental health - Kyprianides, Arabella (International journal of police science & management, 2025)
Whereas existing literature has pointed to a connection between policing and adverse mental health outcomes, it primarily focuses on Black populations within the context of disproportionate police contact and the policing of racially minoritised communities. We conducted a rapid evidence assessment of the literature examining the association between policing and mental health, encompassing individuals of all races, ages and countries, with a focus on investigating the effect of police activity on people's mental health. We include situations in which police are both the proximate cause of (poor) mental health and those in which police are interacting with people who already have poor mental health. A total of 92 studies exploring the impact of police activity on the mental well-being of the policed were included. Overall, the evidence underscores a connection between police encounters and negative mental health repercussions. Quantitative investigations substantiate this correlation, while qualitative studies offer insights into the experiences of individuals who have directly experienced or been privy to accounts of what they often perceive as unjust policing practices. Implications and directions for future research are discussed.